A method for preparing a nonstick coating for a cookware based on amorphous alloy
Patent Information
- Application Number
- CN202611348396.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-27
AI Technical Summary
目前常规的大气等离子喷涂或高速氧燃料喷涂工艺难以同时满足非晶合金对冷却速率的苛刻要求,涂层中非晶相保留率往往不理想
[0029]激光织构化处理在锅具基体表面加工出微米级凹坑阵列,这一粗化结构在后续超音速火焰喷涂过程中能够显著增加非晶合金熔融粒子撞击基体时的铺展附着面积,熔融粒子嵌入凹坑内部并凝固后形成机械互锁锚固点,使复合涂层与锅具基体之间的界面结合状态得到改善。不同于常规喷砂粗化所形成的随机、无序表面形貌,激光织构化凹坑阵列具有规则的几何轮廓和可精确调控的分布密度,当涂层受到烹饪过程中局部刮擦或温差应力作用时,规则分布的凹坑结构能够引导应力沿凹坑边缘均匀耗散,减少应力在界面局部区域的过度集中,降低涂层剥落的风险。同时,规则凹坑阵列在基体表面构建了三维立体拓扑框架,超音速火焰喷涂的熔融粒子在高速撞击凹坑侧壁时发生塑性变形并填充凹坑内部,凝固后形成类似“钉扎”结构的界面结合形态,该形态对涂层整体抗剥离能力产生了实质性贡献。
Smart Images

Figure CN122979807A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of kitchen cookware surface treatment technology, specifically a method for preparing a durable non-stick coating for cookware based on amorphous alloys. Background Technology
[0002] Non-stick pans have become an indispensable cooking utensil in modern kitchens due to their advantages such as food not easily sticking and easy cleaning. The core technology of traditional non-stick pans involves coating the surface of the pan with a low surface energy material. Currently, the mainstream non-stick coatings on the market are mainly divided into two categories: organic coatings and inorganic coatings. Organic coatings are represented by polytetrafluoroethylene (PTFE, Teflon) coatings, which give the pans excellent non-stick properties due to their extremely low surface free energy. However, PTFE coatings have low hardness and poor scratch resistance. The use of metal spatulas during cooking, stirring hard ingredients, and friction during daily cleaning can easily cause scratches or peeling of the coating, leading to a sharp decline in non-stick performance and a generally shorter lifespan. More importantly, PTFE coatings begin to decompose at temperatures exceeding 260°C. Under extreme cooking conditions such as dry heating or high-temperature frying, the coating may release perfluorinated compound fumes that are harmful to human health. Although inorganic ceramic coatings have good temperature resistance, their surface energy is relatively high, their initial non-stick properties are inferior to PTFE, and the coatings are brittle and prone to micro-cracks due to thermal deformation of the pot or temperature difference impact, which affects long-term reliability.
[0003] To address the aforementioned issues, researchers have explored the application of amorphous alloys in non-stick cookware coatings. Amorphous alloys (also known as metallic glasses) possess a structure characterized by short-range atomic order and long-range disorder, lacking crystal defects such as grain boundaries and dislocations, thus exhibiting isotropic surface properties. The surface atoms of amorphous alloys are in a thermodynamically metastable state, exhibiting high surface activity. They can rapidly react with oxygen in the air to form a dense, uniform, and chemically inert oxide film. This oxide film displays low adhesion at the microscopic level, making it difficult for strong chemical bonds or physical anchoring to form at the food contact interface. Furthermore, amorphous alloys possess hardness and elastic limits far exceeding those of traditional metallic materials (such as stainless steel and titanium alloys) on a macroscopic scale, effectively resisting mechanical damage to the coating caused by scraping with spatulas and impacts from hard objects during cooking. These characteristics make amorphous alloys a potential non-stick coating material that combines low adhesion and high wear resistance.
[0004] However, applying amorphous alloys as coatings to cookware surfaces still faces numerous technical challenges. On one hand, during thermal spraying, amorphous alloy powder exhibits a significant tendency to crystallize as it travels through high-temperature flames. When the amorphous phase content decreases, the precipitated crystalline phase in the coating disrupts the uniformity and chemical inertness of the structure, leading to increased surface adhesion. Currently, conventional atmospheric plasma spraying or high-speed oxy-fuel spraying processes cannot simultaneously meet the stringent cooling rate requirements of amorphous alloys, resulting in unsatisfactory amorphous phase retention rates in the coating. On the other hand, the surface energy of amorphous alloy coatings is still higher than that of organic coatings. Relying solely on the material's inherent low adhesion properties is insufficient to achieve satisfactory non-stick cooking results. Furthermore, thermally sprayed coatings inevitably possess a certain degree of porosity and surface roughness. These microscopic morphological features easily become physical anchors for food juices to penetrate and for caramel to adhere during cooking, accelerating the degradation of non-stick properties. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing a durable non-stick coating for cookware based on amorphous alloys, so as to solve the problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides a method for preparing a durable non-stick coating for cookware based on an amorphous alloy, the method comprising:
[0007] Laser texturing is applied to the surface of the cookware substrate to form a roughened surface with an array of micron-sized pits;
[0008] Amorphous alloy powder is mixed with a pore-forming agent and deposited on the roughened surface using a supersonic flame spraying method to form a composite coating.
[0009] The cookware with the composite coating deposited on it is subjected to pulsed electron beam irradiation treatment, which causes the surface of the composite coating to remelt instantaneously. It is then cooled in a protective atmosphere to obtain a surface coating with an amorphous-nanocrystalline composite structure.
[0010] Preferably, the step of laser texturing the surface of the cookware substrate includes:
[0011] A pulsed fiber laser with a laser power of 20W~50W, a scanning speed of 100mm / s~500mm / s, and a pulse frequency of 50kHz~200kHz is used to process circular pits with a diameter of 50μm~200μm and a depth of 10μm~50μm on the surface of the cookware substrate. The center-to-center distance between adjacent pits is 100μm~400μm.
[0012] Preferably, the composition of the amorphous alloy powder, by atomic percentage, is: Zr 45%~65%, Cu 15%~30%, Al 5%~15%, Ni 5%~15%, with the balance being unavoidable impurities;
[0013] The amorphous alloy powder has a particle size distribution of 15μm to 65μm and an amorphous phase content of ≥90%.
[0014] Preferably, the pore-forming agent is polymethyl methacrylate microspheres or polystyrene microspheres, and the microsphere particle size is 10μm~50μm;
[0015] The mass ratio of the amorphous alloy powder to the pore-forming agent is 100:(5~25). The mixing method is to ultrasonically stir the powder in anhydrous ethanol for 20 min to 60 min, and then vacuum dry it at 60℃ to 90℃ for 4 h to 12 h.
[0016] Preferably, in the supersonic flame spraying method, the oxygen flow rate is 300L / min~600L / min, the kerosene flow rate is 0.2L / min~0.5L / min, the powder feeding rate is 20g / min~60g / min, the spraying distance is 150mm~350mm, the flame temperature is 2500℃~3200℃, and the thickness of the obtained composite coating is 80μm~250μm.
[0017] Preferably, the pulsed electron beam irradiation treatment step includes:
[0018] Place the cookware in a vacuum chamber and evacuate the vacuum to 1×10⁻³Pa~5×10⁻³Pa;
[0019] The electron beam accelerating voltage is 25kV~40kV, the pulse frequency is 1Hz~10Hz, the pulse width is 2μs~10μs, the energy density is 2J / cm²~8J / cm², the number of irradiation pulses is 5~30, and the depth of the melt layer on the surface of the composite coating that is instantaneously remelted is 1μm~15μm.
[0020] Preferably, the protective atmosphere is argon gas with a purity of ≥99.99%, the cooling rate is 10K / s~100K / s, the cooling time to room temperature is 60s~300s, and the volume fraction of nanocrystals in the amorphous-nanocrystalline composite structure is 5%~30%, and the nanocrystal size is 5nm~50nm.
[0021] Preferably, before performing laser texturing on the surface of the cookware substrate, the process further includes pre-treatment of the surface of the cookware substrate by degreasing and sandblasting roughening.
[0022] The degreasing process involves ultrasonic cleaning in an acetone solution for 10 to 30 minutes.
[0023] The sandblasting roughening process involves spraying white corundum abrasive onto the inner surface of the cookware at a pressure of 0.2 MPa to 0.6 MPa, with a spraying distance of 100 mm to 200 mm and a spraying angle of 60° to 90°. The resulting surface roughness Ra is 2.5 μm to 6.5 μm.
[0024] Preferably, after the supersonic flame spraying method deposits the composite coating and before the pulsed electron beam irradiation treatment, the composite coating is further subjected to a pre-polishing treatment.
[0025] The pre-polishing treatment uses diamond polishing paste with a particle size of 0.5μm~2μm for mechanical polishing for 5min~20min. After polishing, the surface roughness Ra of the composite coating is reduced to 0.8μm~2.0μm.
[0026] Preferably, after the pulsed electron beam irradiation treatment is completed and cooled to room temperature, the surface coating is further subjected to fluorination treatment;
[0027] The fluorination treatment is as follows: the cookware is placed in a vacuum heating furnace, and an F2 / N2 mixed gas with a flow rate of 50 mL / min to 200 mL / min is introduced, wherein the volume fraction of F2 is 5% to 20%, and heated to 150℃ to 350℃ and held for 30 min to 120 min, thereby forming a metal fluoride surface layer with a thickness of 2 nm to 20 nm on the surface coating.
[0028] Compared with the prior art, the beneficial effects of the present invention are:
[0029] Laser texturing creates a micron-scale array of pits on the surface of the cookware substrate. This roughened structure significantly increases the spreading and adhesion area of molten amorphous alloy particles impacting the substrate during subsequent supersonic flame spraying. The molten particles embed themselves within the pits and solidify, forming mechanically interlocking anchor points, thus improving the interfacial bonding between the composite coating and the cookware substrate. Unlike the random and disordered surface morphology formed by conventional sandblasting, the laser-textured pit array has a regular geometric contour and a precisely controllable distribution density. When the coating is subjected to localized scratching or thermal stress during cooking, the regularly distributed pit structure guides the stress to dissipate evenly along the pit edges, reducing excessive stress concentration in localized areas of the interface and lowering the risk of coating peeling. Simultaneously, the regular pit array constructs a three-dimensional topological framework on the substrate surface. When the molten particles from the supersonic flame spraying impact the pit sidewalls at high speed, they undergo plastic deformation and fill the pits, forming a "pinned" interfacial bonding morphology after solidification. This morphology substantially contributes to the overall peel resistance of the coating.
[0030] In supersonic flame spraying, amorphous alloy powder and a pore-forming agent are mixed and co-deposited to form a composite coating. The pore-forming agent undergoes pyrolysis and vaporization in the high-temperature environment of the spraying flame, leaving diffusely distributed micron-sized pores within the coating. These pores are not coating defects in the traditional sense, but rather serve as buffer spaces for the volume expansion of the molten layer and the flow of the melt during subsequent pulsed electron beam irradiation, preventing macroscopic cracking caused by the accumulation of thermal stress within the coating during instantaneous remelting. Furthermore, when the coating undergoes repeated cooking heating and cooling cycles, the diffused pores can absorb the thermal mismatch strain caused by the difference in thermal expansion coefficients between the cookware substrate and the coating, slowing down the initiation and propagation rate of thermal fatigue cracks, allowing the coating to maintain structural integrity during long-term use. The synergistic control of flame temperature and particle velocity in supersonic flame spraying allows the amorphous alloy powder to maintain a high amorphous phase content during deposition. The endothermic effect of the pyrolysis of the pore-forming agent also provides a certain cooling effect on the sprayed particles, which is beneficial for inhibiting oxygen-induced crystallization of the amorphous phase.
[0031] Pulsed electron beam irradiation is a key post-processing step in this invention to achieve a leap in the non-stick properties of the coating surface. The electron beam deposits energy onto the surface of the composite coating in an extremely short time, causing the micrometer-thick surface layer to remelt instantaneously, followed by rapid solidification at a high cooling rate in a protective atmosphere. This process brings about beneficial changes on at least three levels. First, during the rapid solidification process, nanoscale grains are precipitated in situ in some of the amorphous matrix, forming an amorphous-nanocrystalline composite structure. The introduction of nanocrystals provides additional strengthening effects to the coating surface while maintaining the low-adhesion intrinsic properties of the amorphous phase. As rigid points uniformly embedded in the amorphous matrix, the nanocrystals can improve the surface's resistance to deformation without significantly altering the surface chemical state. When a spatula or hard food comes into contact with the coating surface, the nanocrystals effectively distribute the contact stress, slowing down the adhesive wear and abrasive wear rate of the amorphous matrix. Secondly, the instantaneous remelting process melts and seals the inherent rough peaks and open pores on the surface of the sprayed coating, significantly reducing surface roughness. This reduces the physical anchoring sites where food juices can penetrate the microscopic depressions of the coating and cause charring. The actual contact area between food and the coating decreases during cooking, thus reducing adhesion tendency. Thirdly, the rapid solidification of the remelted layer preserves the high degree of disorder and chemical homogeneity of the amorphous phase structure, resulting in a denser and more complete surface oxide film. This oxide film itself has low surface energy, which, combined with the dispersion strengthening effect of nanocrystals, gives the coating surface superior anti-adhesion and anti-scratch performance while maintaining chemical inertness. Attached Figure Description
[0032] Figure 1 This diagram illustrates the working steps of a method for preparing a durable non-stick coating for cookware based on amorphous alloys, as described in this invention. Detailed Implementation
[0033] The following detailed and complete description of a method for preparing a durable non-stick coating for cookware based on amorphous alloys, in conjunction with specific embodiments and comparative examples, illustrates the present invention. The scope of protection of this invention includes, but is not limited to, the following embodiments. Those skilled in the art can make routine minor adjustments to the technical parameters without departing from the core technical concept of this invention, all of which fall within the scope of protection of this invention.
[0034] All embodiments and comparative examples of this invention use the same 304 stainless steel cookware substrate with a thickness of 2mm. The inner surface of the cookware is the working surface to be coated. All pretreatment procedures are based on the same standard to ensure the uniqueness of experimental variables. The specific pretreatment steps are as follows:
[0035] (1) Ultrasonic degreasing treatment: The stainless steel cookware substrate is completely immersed in acetone solution and ultrasonically cleaned using an ultrasonic cleaner at room temperature to remove oil, dust and oxide impurities from the substrate surface. After cleaning, the substrate is removed and the surface is dried with high-purity nitrogen.
[0036] (2) Sandblasting roughening pretreatment: White corundum sand is used to sandblast the inner surface of the pot after degreasing. The air pressure, spray distance and angle of the sandblasting equipment are adjusted to complete the roughening of the substrate and improve the bonding strength between the substrate and the subsequent coating. After sandblasting, the residual sand particles and impurities on the surface are blown away and ready for use.
[0037] Example 1
[0038] See appendix Figure 1 This embodiment provides a method for preparing a durable non-stick coating for cookware based on amorphous alloys. The specific preparation steps are as follows:
[0039] S1. Pretreatment of cookware substrate: The 304 stainless steel cookware substrate is ultrasonically cleaned in acetone solution for 10 minutes to remove oil from the surface; then, it is roughened by sandblasting with white corundum sand at 0.2MPa air pressure, with a spraying distance of 100mm and a spraying angle of 60°. After treatment, the surface roughness Ra of the substrate is 2.5μm. After blowing away the surface impurities, it is ready for use.
[0040] S2. Laser texturing and roughening treatment: A pulsed fiber laser is used to texture the pre-treated cookware substrate surface. The laser process parameters are set as follows: laser power 20W, scanning speed 100mm / s, pulse frequency 50kHz. A uniformly distributed array of circular micron-sized pits is processed on the substrate surface. The diameter of a single pit is 50μm and the depth is 10μm. The center-to-center distance between adjacent pits is 100μm, forming a regular micron-sized roughened surface.
[0041] S3. Preparation of amorphous alloy composite powder: Amorphous alloy powder was selected, with the following composition by atomic percentage: Zr 45%, Cu 30%, Al 15%, Ni 10%, free of additional impurities, amorphous phase content of 92%, and powder particle size distribution of 15μm~30μm; polymethyl methacrylate microspheres with a particle size of 10μm were selected as pore-forming agents, and the powder was prepared according to a mass ratio of amorphous alloy powder to pore-forming agent of 100:5; the mixed powder was placed in anhydrous ethanol solution and ultrasonically stirred for 20min to ensure uniform dispersion of the powder, and then transferred to a vacuum drying oven and vacuum dried at 60℃ for 12h to completely remove the ethanol solvent, resulting in a uniformly dried composite spray powder.
[0042] S4. Supersonic flame spraying deposition of composite coating: Using supersonic flame spraying equipment, the prepared composite powder is sprayed onto the roughened surface of the cookware after laser texturing treatment. The spraying process parameters are set as follows: oxygen flow rate 300L / min, kerosene flow rate 0.2L / min, powder feeding rate 20g / min, spraying distance 150mm, flame temperature 2500℃, and continuous spraying until the coating thickness is 80μm to complete the deposition of composite coating.
[0043] S5. Coating pre-polishing treatment: The surface of the deposited composite coating is mechanically polished using diamond polishing paste with a particle size of 0.5μm for 5 minutes. After polishing, the surface roughness Ra of the coating is reduced to 0.8μm, removing protruding particles, pores and burrs from the coating surface to ensure the smoothness of the coating surface.
[0044] S6. Pulsed Electron Beam Irradiation Treatment: Place the pre-polished cookware in the vacuum chamber of the vacuum electron beam treatment equipment and evacuate to a vacuum degree of 1×10⁻³Pa; set the electron beam process parameters: accelerating voltage 25kV, pulse frequency 1Hz, pulse width 2μs, energy density 2J / cm², irradiation pulse number 5 times, so that the surface of the composite coating undergoes instantaneous remelting and the melt layer depth is 1μm.
[0045] S7. Controlled cooling and forming: After irradiation, 99.99% pure argon gas is introduced into the vacuum chamber as a protective atmosphere, and the cooling rate is controlled at 10K / s. The cooling is continued for 300s to room temperature. After cooling, the coating forms an amorphous-nanocrystalline composite structure, in which the nanocrystal integral is 5% and the average size of the nanocrystals is 5nm.
[0046] S8. Surface fluorination modification treatment: The cooled cookware is transferred to a vacuum heating furnace, and F2 / N2 mixed gas is introduced at a flow rate of 50 mL / min, wherein the volume fraction of F2 is 5%; the temperature is raised to 150℃ and held for 120 min to generate a 2 nm thick metal fluoride surface layer on the coating surface, and finally an amorphous alloy cookware coating with durable non-stick properties is obtained.
[0047] Example 2
[0048] This embodiment provides a method for preparing a durable non-stick coating for cookware based on amorphous alloys. The specific preparation steps are as follows:
[0049] S1. Pretreatment of cookware substrate: The 304 stainless steel cookware substrate is ultrasonically cleaned in acetone solution for 20 minutes to remove oil from the surface; then, it is roughened by sandblasting with white corundum sand at 0.4MPa air pressure, with a spraying distance of 150mm and a spraying angle of 75°. After treatment, the surface roughness Ra of the substrate is 4.5μm. After blowing away the surface impurities, it is ready for use.
[0050] S2. Laser texturing and roughening treatment: A pulsed fiber laser is used to texture the pre-treated cookware substrate surface. The laser process parameters are set as follows: laser power 35W, scanning speed 300mm / s, pulse frequency 120kHz. A uniformly distributed array of circular micron-sized pits is processed on the substrate surface. The diameter of a single pit is 120μm, the depth is 30μm, and the center-to-center distance between adjacent pits is 250μm, forming a regular micron-sized roughened surface.
[0051] S3. Preparation of amorphous alloy composite powder: Amorphous alloy powder was selected, with the following composition by atomic percentage: Zr 55%, Cu 22%, Al 10%, Ni 13%, with the balance being unavoidable trace impurities. The amorphous phase content was 95%, and the powder particle size distribution was 30μm~50μm. Polystyrene microspheres with a particle size of 30μm were selected as pore-forming agents and were prepared according to a mass ratio of amorphous alloy powder to pore-forming agent of 100:15. The mixed powder was placed in anhydrous ethanol solution and ultrasonically stirred for 40 minutes to ensure uniform dispersion of the powder. Then, it was transferred to a vacuum drying oven and vacuum dried at 75℃ for 8 hours to completely remove the ethanol solvent, resulting in a uniformly dried composite spray powder.
[0052] S4. Supersonic Flame Spraying Deposition of Composite Coating: Using supersonic flame spraying equipment, the prepared composite powder is sprayed onto the roughened surface of the cookware after laser texturing treatment. The spraying process parameters are set as follows: oxygen flow rate 450L / min, kerosene flow rate 0.35L / min, powder feeding rate 40g / min, spraying distance 250mm, flame temperature 2850℃, and continuous spraying until the coating thickness is 160μm to complete the deposition of the composite coating.
[0053] S5. Coating pre-polishing treatment: The surface of the deposited composite coating is mechanically polished using diamond polishing paste with a particle size of 1.2μm for 12 minutes. After polishing, the surface roughness Ra of the coating is reduced to 1.4μm, removing protruding particles, pores and burrs from the coating surface to ensure the smoothness of the coating surface.
[0054] S6. Pulsed Electron Beam Irradiation Treatment: Place the pre-polished cookware in the vacuum chamber of the vacuum electron beam treatment equipment and evacuate to a vacuum degree of 3×10⁻³Pa; set the electron beam process parameters: accelerating voltage 32kV, pulse frequency 5Hz, pulse width 6μs, energy density 5J / cm², irradiation pulse count 18 times, so that the surface of the composite coating undergoes instantaneous remelting and the melt layer depth is 8μm.
[0055] S7. Controlled cooling and forming: After irradiation, 99.99% pure argon gas is introduced into the vacuum chamber as a protective atmosphere, and the cooling rate is controlled at 55K / s. The cooling is continued for 180s to room temperature. After cooling, the coating forms an amorphous-nanocrystalline composite structure, in which the nanocrystal integral is 18% and the average size of the nanocrystals is 25nm.
[0056] S8. Surface fluorination modification treatment: The cooled cookware is transferred to a vacuum heating furnace, and F2 / N2 mixed gas is introduced at a flow rate of 120 mL / min, wherein the volume fraction of F2 is 12%; the temperature is raised to 250℃ and held for 75 min, and a metal fluoride surface layer with a thickness of 11 nm is generated on the coating surface, and finally an amorphous alloy cookware coating with durable non-stick properties is obtained.
[0057] Example 3
[0058] This embodiment provides a method for preparing a durable non-stick coating for cookware based on amorphous alloys. The specific preparation steps are as follows:
[0059] S1. Pretreatment of cookware substrate: The 304 stainless steel cookware substrate is ultrasonically cleaned in acetone solution for 30 minutes to remove oil from the surface; then, it is roughened by sandblasting with white corundum sand at 0.6MPa air pressure, with a spraying distance of 200mm and a spraying angle of 90°. After treatment, the surface roughness Ra of the substrate is 6.5μm. After blowing away the surface impurities, it is ready for use.
[0060] S2. Laser texturing and roughening treatment: A pulsed fiber laser is used to texture the pre-treated cookware substrate surface. The laser process parameters are set as follows: laser power 50W, scanning speed 500mm / s, pulse frequency 200kHz. A uniformly distributed array of circular micron-sized pits is processed on the substrate surface. The diameter of a single pit is 200μm and the depth is 50μm. The center-to-center distance between adjacent pits is 400μm, forming a regular micron-sized roughened surface.
[0061] S3. Preparation of amorphous alloy composite powder: Amorphous alloy powder was selected, with the following composition by atomic percentage: Zr 65%, Cu 15%, Al 5%, Ni 15%, with the balance being unavoidable trace impurities. The amorphous phase content was 93%, and the powder particle size distribution was 50μm~65μm. Polymethyl methacrylate microspheres with a particle size of 50μm were selected as pore-forming agents and prepared according to a mass ratio of amorphous alloy powder to pore-forming agent of 100:25. The mixed powder was placed in anhydrous ethanol solution and ultrasonically stirred for 60 minutes to ensure uniform dispersion of the powder. Then, it was transferred to a vacuum drying oven and vacuum dried at 90℃ for 4 hours to completely remove the ethanol solvent, resulting in a uniformly dried composite spray powder.
[0062] S4. Supersonic Flame Spraying Deposition of Composite Coating: Using supersonic flame spraying equipment, the prepared composite powder is sprayed onto the roughened surface of the cookware after laser texturing treatment. The spraying process parameters are set as follows: oxygen flow rate 600L / min, kerosene flow rate 0.5L / min, powder feeding rate 60g / min, spraying distance 350mm, flame temperature 3200℃, and continuous spraying until the coating thickness is 250μm to complete the deposition of the composite coating.
[0063] S5. Coating pre-polishing treatment: The surface of the deposited composite coating is mechanically polished using diamond polishing paste with a particle size of 2μm for 20 minutes. After polishing, the surface roughness Ra of the coating is reduced to 2.0μm, removing protruding particles, pores and burrs from the coating surface to ensure the smoothness of the coating surface.
[0064] S6. Pulsed Electron Beam Irradiation Treatment: Place the pre-polished cookware in the vacuum chamber of the vacuum electron beam treatment equipment and evacuate to a vacuum degree of 5×10⁻³Pa; set the electron beam process parameters: accelerating voltage 40kV, pulse frequency 10Hz, pulse width 10μs, energy density 8J / cm², irradiation pulse count 30 times, so that the surface of the composite coating undergoes instantaneous remelting and the melt layer depth is 15μm.
[0065] S7. Controlled cooling and forming: After irradiation, 99.99% pure argon gas is introduced into the vacuum chamber as a protective atmosphere, and the cooling rate is controlled at 100K / s. The cooling is continued for 60s to room temperature. After cooling, the coating forms an amorphous-nanocrystalline composite structure, in which the nanocrystal integral is 30% and the average size of the nanocrystals is 50nm.
[0066] S8. Surface fluorination modification treatment: The cooled cookware is transferred to a vacuum heating furnace, and F2 / N2 mixed gas is introduced at a flow rate of 200 mL / min, wherein the volume fraction of F2 is 20%; the temperature is raised to 350℃ and held for 30 min to generate a 20 nm thick metal fluoride surface layer on the coating surface, and finally an amorphous alloy cookware coating with durable non-stick properties is obtained.
[0067] Example 4
[0068] This embodiment provides a method for preparing a durable non-stick coating for cookware based on amorphous alloys. The specific preparation steps are as follows:
[0069] S1. Pretreatment of cookware substrate: The 304 stainless steel cookware substrate is ultrasonically cleaned in acetone solution for 25 minutes to remove oil from the surface; then, it is roughened by sandblasting with white corundum sand at 0.5MPa air pressure, with a spraying distance of 180mm and a spraying angle of 80°. After treatment, the surface roughness Ra of the substrate is 5.5μm. After blowing away the surface impurities, it is ready for use.
[0070] S2. Laser texturing and roughening treatment: A pulsed fiber laser is used to texture the pre-treated cookware substrate surface. The laser process parameters are set as follows: laser power 40W, scanning speed 400mm / s, pulse frequency 150kHz. A uniformly distributed array of circular micron-sized pits is processed on the substrate surface. The diameter of a single pit is 150μm, the depth is 40μm, and the center-to-center distance between adjacent pits is 320μm, forming a regular micron-sized roughened surface.
[0071] S3. Preparation of amorphous alloy composite powder: Amorphous alloy powder was selected, with the following composition by atomic percentage: Zr 50%, Cu 25%, Al 12%, Ni 13%, with the balance being unavoidable trace impurities. The amorphous phase content was 94%, and the powder particle size distribution was 20μm~55μm. Polystyrene microspheres with a particle size of 40μm were selected as pore-forming agents and were prepared according to a mass ratio of amorphous alloy powder to pore-forming agent of 100:20. The mixed powder was placed in anhydrous ethanol solution and ultrasonically stirred for 50 minutes to ensure uniform dispersion of the powder. Then, it was transferred to a vacuum drying oven and vacuum dried at 80℃ for 6 hours to completely remove the ethanol solvent, resulting in a uniformly dried composite spray powder.
[0072] S4. Supersonic flame spraying deposition of composite coating: Using supersonic flame spraying equipment, the prepared composite powder is sprayed onto the roughened surface of the cookware after laser texturing treatment. The spraying process parameters are set as follows: oxygen flow rate 520L / min, kerosene flow rate 0.42L / min, powder feeding rate 50g / min, spraying distance 300mm, flame temperature 3000℃, and continuous spraying until the coating thickness is 200μm to complete the deposition of the composite coating.
[0073] S5. Coating pre-polishing treatment: The surface of the deposited composite coating is mechanically polished using diamond polishing paste with a particle size of 1.5μm for 15 minutes. After polishing, the surface roughness Ra of the coating is reduced to 1.6μm, removing protruding particles, pores and burrs from the coating surface to ensure the smoothness of the coating surface.
[0074] S6. Pulsed Electron Beam Irradiation Treatment: Place the pre-polished cookware in the vacuum chamber of the vacuum electron beam treatment equipment and evacuate to a vacuum degree of 4×10⁻³Pa; set the electron beam process parameters: accelerating voltage 35kV, pulse frequency 8Hz, pulse width 8μs, energy density 6.5J / cm², irradiation pulse count 22 times, causing instantaneous remelting of the composite coating surface, with a melt layer depth of 12μm.
[0075] S7. Controlled cooling and forming: After irradiation, 99.99% pure argon gas is introduced into the vacuum chamber as a protective atmosphere, and the cooling rate is controlled at 80K / s. The cooling is continued for 120s to room temperature. After cooling, the coating forms an amorphous-nanocrystalline composite structure, in which the nanocrystal integral is 22% and the average size of the nanocrystals is 38nm.
[0076] S8. Surface fluorination modification treatment: The cooled cookware is transferred to a vacuum heating furnace, and F2 / N2 mixed gas is introduced at a flow rate of 160 mL / min, wherein the volume fraction of F2 is 16%; the temperature is raised to 300℃ and held for 50 min to generate a 15 nm thick metal fluoride surface layer on the coating surface, and finally an amorphous alloy cookware coating with durable non-stick properties is obtained.
[0077] Comparative Example 1 (without laser texturing treatment)
[0078] This comparative example provides a method for preparing a cookware coating, which is basically the same as the process in Example 2, except that the laser texturing roughening process is omitted. The substrate only retains the roughened surface after sandblasting pretreatment and directly proceeds to the subsequent supersonic flame spraying, polishing, electron beam irradiation, cooling, and fluorination processes. The remaining process parameters are exactly the same as in Example 2. The specific steps are briefly described below:
[0079] S1. Pretreatment of cookware substrate: The degreasing and sandblasting process is exactly the same as in Example 2. After treatment, the surface roughness Ra of the substrate is 4.5μm.
[0080] S2. Laser texturing treatment is omitted, and the process proceeds directly to the composite powder coating process;
[0081] The process parameters for S3-S8, composite powder preparation, supersonic flame spraying, pre-polishing, electron beam irradiation, controlled cooling, and fluorination treatment are all completely consistent with those in Example 2, and a cookware coating without laser texture modification is finally prepared.
[0082] Comparative Example 2 (treatment without pulsed electron beam irradiation)
[0083] This comparative example provides a method for preparing a cookware coating, which is basically the same as the process in Example 2, except that the pulsed electron beam irradiation treatment step is omitted, and the coating is directly subjected to protective atmosphere cooling and fluorination treatment after pre-polishing. The remaining process parameters are exactly the same as in Example 2. The specific steps are briefly described as follows:
[0084] S1-S5, substrate pretreatment, laser texturing, composite powder preparation, supersonic flame spraying, and pre-polishing processes are completely consistent with those in Example 2;
[0085] S6. Omit the pulsed electron beam irradiation remelting process;
[0086] S7-S8, the cooling parameters and fluorination treatment parameters of Example 2 were directly used for subsequent processing, and finally, a cookware coating without electron beam remelting modification was prepared.
[0087] Comparative Example 3 (without surface fluorination treatment)
[0088] This comparative example provides a method for preparing a cookware coating, which is basically the same as the process in Example 2, except that the final surface fluorination modification treatment is omitted, and the finished coating is obtained directly after electron beam irradiation and cooling to room temperature. The remaining process parameters are exactly the same as in Example 2. The specific steps are briefly described below:
[0089] S1-S7, substrate pretreatment, laser texturing, composite powder preparation, supersonic flame spraying, pre-polishing, electron beam irradiation, and controllable cooling processes are completely consistent with those in Example 2;
[0090] S8. The fluorination modification process is omitted, and the finished product is prepared directly, resulting in a cookware coating with a fluoride-free surface modification.
[0091] To verify the comprehensive performance of the coating prepared by this invention, performance tests were uniformly conducted on all examples and comparative samples. The core test indicators included: coating adhesion strength, coating hardness, surface water contact angle (characterizing non-stickiness), number of wear cycles (characterizing durability), and coating porosity. All tests were conducted using the same testing equipment and the same testing standards. Each group of samples was tested 5 times, and the average value was taken as the final test data to eliminate the interference of experimental errors.
[0092] Test standards: Coating bonding strength is tested according to GB / T 8642-2002 Thermal spray coating bonding strength test standard; coating hardness is tested using a Vickers hardness tester; water contact angle is tested using an optical contact angle measuring instrument; wear resistance is tested using a reciprocating wear tester with a stainless steel abrasive head, a load of 5N, a single reciprocating stroke of 10mm, and the number of cycles when the coating breaks and peels off is recorded; coating porosity is detected using metallographic image analysis.
[0093] Table 1: Basic physical property parameters of coatings in each embodiment and comparative example
[0094] Example 1 48.6 892 2.13 0.82 Example 2 55.3 968 1.56 1.41 Example 3 51.2 925 1.89 2.02 Example 4 53.7 951 1.68 1.63 Comparative Example 1 32.5 816 3.75 2.86 Comparative Example 2 41.8 853 2.92 2.15 Comparative Example 3 54.9 965 1.58 1.43
[0095] Based on the test data in Table 1, it can be seen that the coating prepared by the synergistic process of laser texturing, electron beam irradiation remelting, and fluorination modification in this invention possesses excellent basic physical properties. The technical gains and parameter influence laws of each process are as follows:
[0096] Comparing the data from Comparative Example 1 and Example 2 clearly demonstrates the core role of laser texturing. After omitting the laser texturing process, the coating adhesion strength decreased significantly from 55.3 MPa to 32.5 MPa, a reduction of over 41%, while the coating porosity increased from 1.56% to 3.75%, and the surface roughness significantly increased. This is because laser texturing constructs a regular array of micron-sized pits on the substrate surface, forming a mechanical interlocking structure that greatly improves the adhesion between the substrate and the coating. Simultaneously, the regular texture morphology optimizes the uniformity of powder deposition, reduces porosity and voids during coating formation, lowers porosity, and improves coating density. Without laser texturing, the substrate only relies on sandblasting for roughening, resulting in a chaotic surface morphology, uneven powder deposition, weak interfacial adhesion, and numerous defects.
[0097] Comparing the data from Comparative Example 2 and Example 2 verifies the modification effect of pulsed electron beam irradiation. Without electron beam irradiation and remelting, the coating hardness decreased from 968 HV to 853 HV, the bonding strength decreased, and the porosity significantly increased. Pulsed electron beams can achieve instantaneous remelting of the coating surface, rapidly solidifying to form an amorphous-nanocrystalline composite structure, refining the coating grains, eliminating defects such as interlayer porosity and microcracks generated during spraying, and improving the coating's density and mechanical strength. The coating without electron beam treatment retains the layered stacking structure of the sprayed state, with numerous internal defects, coarse grains, and significantly deteriorated mechanical properties.
[0098] Comparing the data of Comparative Example 3 and Example 2, it can be seen that fluorination treatment has no significant negative impact on the basic physical properties of the coating. The coating bonding strength, hardness, and porosity remain basically consistent, indicating that fluorination modification is a surface functional modification. It only forms a nanoscale fluoride film on the coating surface and does not change the microstructure and mechanical properties of the coating matrix. It can optimize the surface functional characteristics without sacrificing the mechanical properties of the coating.
[0099] Comparing the data from the four sets of examples, Examples 2 and 4 showed the best overall performance. Example 1 had relatively low bonding strength and hardness due to its smaller process parameters, resulting in a thinner coating and insufficient modification. Example 3 had slightly lower bonding strength and hardness due to its larger process parameters, which caused slight coarsening of local grains during high-energy beam treatment. This demonstrates that the process parameters in the middle range of this invention have the best adaptability and can achieve the optimal match between coating density and mechanical properties.
[0100] Table 2: Non-stick properties and durability parameters of the coatings in each embodiment and comparative example
[0101] Example 1 118.6 12800 Level 0 No peeling or flaking Example 2 126.3 18600 Level 0 No peeling, no flaking, no discoloration Example 3 122.5 16300 Level 0 No peeling, slight discoloration Example 4 124.8 17900 Level 0 No peeling or flaking Comparative Example 1 105.2 7200 Level 2 Mild peeling in some areas Comparative Example 2 112.7 9500 Level 1 No peeling, slight wear Comparative Example 3 98.5 18200 Level 0 No peeling or flaking
[0102] The water contact angle is a core indicator characterizing the non-stick performance of cookware coatings. A larger contact angle indicates stronger surface hydrophobicity and better non-stick properties. The number of abrasion cycles and high-temperature boiling stability are key parameters characterizing the coating's long-term performance and directly determine the cookware's lifespan. Based on the data in Table 2, the following conclusions can be drawn:
[0103] First, fluorination is a core process ensuring the coating's excellent non-stick properties. In Comparative Example 3, omitting fluorination, the water contact angle of the coating was only 98.5°, far lower than the 126.3° of Example 2, resulting in a significant decrease in non-stick performance. This is because fluorination generates a nanoscale metallic fluoride film on the coating surface. Fluorine has extremely low surface energy, which significantly reduces the adhesion of the coating surface and inhibits the adhesion of food and water stains, making it a key modification for achieving long-lasting non-stick performance. Furthermore, the abrasion resistance of Comparative Example 3 was close to that of Example 2, further demonstrating that fluorination only optimizes the surface's hydrophobic and non-stick properties and does not affect the coating's wear resistance and durability.
[0104] Secondly, laser texturing treatment can simultaneously improve the non-stickiness and durability of the coating. In Comparative Example 1, without laser texturing, the coating's water contact angle and abrasion resistance are significantly reduced, and the cross-cut adhesion rating drops to level 2, resulting in peeling defects after high-temperature use. The lack of a regular texture on the substrate leads to poor coating deposition uniformity, disordered microscopic unevenness on the surface, and an inability to form a stable hydrophobic interface. Simultaneously, the interfacial bonding is weak, making the coating prone to wear and peeling failure under long-term abrasion and high-temperature conditions, significantly reducing the durability of the cookware.
[0105] Furthermore, electron beam irradiation modification can significantly improve the durability and wear resistance of the coating. Comparative Example 2, without electron beam remelting modification, has numerous internal defects and a loose structure, resulting in only 9500 wear-resistant cycles, far lower than the 18600 cycles of Example 2, and a simultaneous decrease in surface hydrophobicity. Electron beam remelting refines the grains and densifies the coating structure, improving surface smoothness and structural stability, reducing stress concentration during wear, and significantly enhancing the coating's wear life and operational stability.
[0106] Finally, among the four examples, Example 2 showed the best overall performance in terms of non-stickiness and durability, with the largest water contact angle, the highest number of abrasion cycles, and the best high-temperature stability; Example 1 had lower parameters, insufficient coating modification, and slightly weaker non-stickiness and durability; Example 3 had excessively high parameters, resulting in slightly coarsened coating surface grains and reduced microscopic smoothness, leading to a slight decrease in hydrophobicity and abrasion resistance, further verifying the technical superiority of the preferred parameter range of the present invention.
[0107] Table 3: Microstructure parameters of coatings in each embodiment
[0108] Example 1 5 5 91.2 2 Example 2 18 25 93.5 11 Example 3 30 50 90.8 20 Example 4 22 38 92.6 15
[0109] The core innovation of this invention lies in the preparation of an amorphous-nanocrystalline composite coating. The amorphous phase provides excellent corrosion resistance, wear resistance, and surface smoothness, while the nanocrystalline phase provides excellent mechanical support and structural stability. The two work synergistically to achieve long-term stable coating performance. The microstructure parameters are analyzed in Table 3 as follows:
[0110] With the increase of electron beam irradiation energy density and pulse number, the integral number of nanocrystals and the grain size of the coating show a gradient increasing trend. In Example 1, the electron beam process parameters are the weakest, the nanocrystal integral number is only 5%, and the grain size is only 5nm. The coating is mainly composed of amorphous phase, with excellent structural toughness, but slightly insufficient mechanical support. In Example 3, the electron beam parameters are the strongest, the nanocrystal integral number reaches 30%, and the grain size increases to 50nm. The high proportion of nanocrystals and the large grain size will lead to a decrease in the proportion of amorphous phase in the coating, and a slight decrease in the density and corrosion resistance unique to amorphous materials.
[0111] Examples 2 and 4 exhibit the optimal microstructure composition, with the nanocrystal integral number controlled at 18%–22%, grain size at 25 nm–38 nm, and amorphous phase content maintained above 92%, forming a composite structure of "continuous amorphous phase matrix + uniformly dispersed nanocrystal reinforcement." This structure retains the advantages of amorphous alloys, such as density, low defects, corrosion resistance, and smooth surface, while enhancing coating hardness, structural stability, and wear resistance through dispersed nanocrystals, thus avoiding the drawbacks of insufficient strength in a single amorphous structure and numerous defects and poor non-stickiness in a single crystalline structure.
[0112] Meanwhile, the thickness of the fluorinated layer increases linearly with the improvement of fluorination process parameters. In Example 1, the thickness of the fluorinated layer is only 2nm, which is too thin and has insufficient long-term non-stick stability. In Example 3, the thickness of the fluorinated layer is 20nm, which is too thick and is prone to surface stress concentration and slight peeling. In Example 2, the thickness of the fluorinated layer is 11nm, which is moderate. The modified layer is tightly bonded to the coating substrate and can stably play a low surface energy hydrophobic role. It also has no structural defects and is suitable for long-term use of cookware.
[0113] Simulating the actual high-temperature cooking and acid / alkali corrosion conditions of cookware, high-temperature corrosion tests were conducted on each group of samples (200℃ high-temperature baking for 200h, neutral salt spray test for 100h). The coating corrosion and performance degradation rate were recorded. Specific data are as follows:
[0114] Table 4: Test data on high temperature corrosion resistance and long-term service stability of coatings
[0115] Sample group Performance degradation rate (%) after baking at 200℃ for 200 hours 100h neutral salt spray corrosion rating Coating condition after repeated stir-frying 500 times Oil stain adhesion residue rate (%) Example 1 8.6 Level 9 Slight wear, no peeling 3.2 Example 2 4.2 Level 10 No wear, no discoloration, no peeling 1.1 Example 3 6.5 Level 9 Slight discoloration, no peeling 2.0 Example 4 5.1 Level 10 No significant changes 1.6 Comparative Example 1 18.3 Level 7 Localized wear and peeling 8.7 Comparative Example 2 12.5 Level 8 Obvious wear 5.3 Comparative Example 3 7.8 Level 9 Slight wear 6.2
[0116] Cookware coatings need to withstand long-term high-temperature baking, acid and alkali corrosion from food, and repeated friction and stir-frying in actual use. Therefore, high-temperature stability, corrosion resistance, and anti-oil adhesion are the core indicators for measuring the longevity of the coating's non-stick life. A detailed analysis is provided below based on the data in Table 4:
[0117] The composite process of this invention can significantly improve the high-temperature durability and stability of the coating. The high-temperature performance degradation rate of all four examples was less than 9%, and the salt spray corrosion rating reached level 9 or above. Examples 2 and 4 showed the best performance, with high-temperature degradation rates of only 4.2% and 5.1% respectively, and a salt spray rating of up to level 10. After 500 cycles of repeated heating, the coating showed no significant damage. In contrast, the performance degradation of the comparative examples was significantly increased. Comparative example 1 showed a high-temperature degradation rate as high as 18.3%, and a salt spray rating of only level 7, exhibiting peeling and damage. This fully demonstrates that the synergistic effect of laser texturing, electron beam remelting, and fluorination modification can significantly improve the structural stability and high-temperature corrosion resistance of the coating.
[0118] Fluorination modification is key to reducing oil adhesion and achieving long-lasting non-stick performance. In Comparative Example 3, the oil adhesion residue rate of the non-fluorinated layer was as high as 6.2%, far exceeding the 1.1% of Example 2. During long-term high-temperature use, the non-fluorinated modified coating is prone to oil accumulation and stubborn adhesion, gradually losing its non-stick properties; while the fluorinated modified coating has extremely low surface energy, making it difficult for oil to adhere and easy to clean, maintaining a clean and non-stick state for a long time, and significantly extending the service life of the cookware.
[0119] The amorphous-nanocrystalline composite structure formed by electron beam irradiation can significantly improve the coating's resistance to high temperatures and corrosion. Comparative Example 2 lacks a composite microstructure, resulting in numerous internal defects and a tendency for thermal stress concentration under high-temperature conditions, accelerating coating aging and failure; its performance degradation rate is approximately three times that of Example 2. In contrast, the composite structure of this invention can effectively disperse thermal stress and block the penetration of corrosive media, fundamentally improving the long-term stability of the coating.
[0120] Excessive increases in process parameters can easily lead to a slight decrease in coating stability. In Example 3, due to excessively high electron beam and fluorination process parameters, the nanocrystal size was too large and the fluorination layer was too thick. Under high-temperature conditions, slight thermal discoloration was likely to occur, and the performance degradation rate was slightly higher than that in Examples 2 and 4. This further verifies that the preferred parameter range of the present invention can achieve the optimal match between coating microstructure, surface modification effect, and durability performance.
[0121] Based on the performance test data and microstructure analysis of the above embodiments and comparative examples, it can be determined that the present invention successfully prepared a durable non-stick coating for cookware with an amorphous-nanocrystalline composite structure through a synergistic process of "laser texturing and coarsening + amorphous alloy composite powder spraying + pulsed electron beam remelting modification + controlled cooling + surface fluorination modification". Laser texturing treatment strengthens the interfacial bonding strength between the substrate and the coating, optimizing the coating deposition morphology; supersonic flame spraying achieves uniform deposition of the composite coating; pulsed electron beam irradiation remelting refines the grains and densifies coating defects, forming a high-performance composite microstructure; controlled cooling ensures stable structural formation; and fluorination modification imparts ultra-low surface energy to the coating, achieving a long-lasting non-stick effect.
[0122] Each process step works in synergy and is indispensable. Compared to coatings prepared by a single process, the coating prepared by this invention has multiple advantages, including high bonding strength, high hardness, low porosity, excellent hydrophobicity, wear resistance, high temperature resistance, corrosion resistance, and resistance to oil adhesion. It completely solves the industry pain points of traditional cookware non-stick coatings, such as easy peeling, easy wear, and non-stick failure after short-term use, significantly improving the service life and performance of cookware, and possessing extremely high practical application value and promotion prospects. Among them, the process parameters corresponding to Example 2 of this invention are the optimal process parameters, which can maximize the comprehensive performance of the coating.
[0123] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a durable non-stick coating for cookware based on amorphous alloys, characterized in that, The preparation method includes: Laser texturing is applied to the surface of the cookware substrate to form a roughened surface with an array of micron-sized pits; Amorphous alloy powder is mixed with a pore-forming agent and deposited on the roughened surface using a supersonic flame spraying method to form a composite coating. The cookware with the composite coating deposited on it is subjected to pulsed electron beam irradiation treatment, which causes the surface of the composite coating to remelt instantaneously. It is then cooled in a protective atmosphere to obtain a surface coating with an amorphous-nanocrystalline composite structure.
2. The method for preparing a durable non-stick coating for cookware based on an amorphous alloy according to claim 1, characterized in that, The step of laser texturing the surface of the cookware substrate includes: A pulsed fiber laser with a laser power of 20W~50W, a scanning speed of 100mm / s~500mm / s, and a pulse frequency of 50kHz~200kHz is used to process circular pits with a diameter of 50μm~200μm and a depth of 10μm~50μm on the surface of the cookware substrate. The center-to-center distance between adjacent pits is 100μm~400μm.
3. The method for preparing a durable non-stick coating for cookware based on an amorphous alloy according to claim 1, characterized in that, The composition of the amorphous alloy powder, by atomic percentage, is: Zr 45%~65%, Cu 15%~30%, Al 5%~15%, Ni 5%~15%, with the balance being unavoidable impurities; The amorphous alloy powder has a particle size distribution of 15μm to 65μm and an amorphous phase content of ≥90%.
4. The method for preparing a durable non-stick coating for cookware based on an amorphous alloy according to claim 1, characterized in that, The pore-forming agent is polymethyl methacrylate microspheres or polystyrene microspheres, with a microsphere particle size of 10 μm to 50 μm. The mass ratio of the amorphous alloy powder to the pore-forming agent is 100:(5~25). The mixing method is to ultrasonically stir the powder in anhydrous ethanol for 20 min to 60 min, and then vacuum dry it at 60℃ to 90℃ for 4 h to 12 h.
5. The method for preparing a durable non-stick coating for cookware based on an amorphous alloy according to claim 1, characterized in that, In the supersonic flame spraying method, the oxygen flow rate is 300L / min~600L / min, the kerosene flow rate is 0.2L / min~0.5L / min, the powder feeding rate is 20g / min~60g / min, the spraying distance is 150mm~350mm, the flame temperature is 2500℃~3200℃, and the thickness of the obtained composite coating is 80μm~250μm.
6. The method for preparing a durable non-stick coating for cookware based on an amorphous alloy according to claim 1, characterized in that, The steps of the pulsed electron beam irradiation treatment include: Place the cookware in a vacuum chamber and evacuate the vacuum to 1×10⁻³Pa~5×10⁻³Pa; The electron beam accelerating voltage is 25kV~40kV, the pulse frequency is 1Hz~10Hz, the pulse width is 2μs~10μs, the energy density is 2J / cm²~8J / cm², the number of irradiation pulses is 5~30, and the depth of the melt layer on the surface of the composite coating that is instantaneously remelted is 1μm~15μm.
7. The method for preparing a durable non-stick coating for cookware based on an amorphous alloy according to claim 1, characterized in that, The protective atmosphere is argon gas with a purity of ≥99.99%, the cooling rate is 10K / s~100K / s, the cooling time to room temperature is 60s~300s, and the volume fraction of nanocrystals in the amorphous-nanocrystalline composite structure is 5%~30%, and the nanocrystal size is 5nm~50nm.
8. The method for preparing a durable non-stick coating for cookware based on an amorphous alloy according to claim 1, characterized in that, Before performing laser texturing on the surface of the cookware substrate, the process also includes pretreatment of the surface of the cookware substrate by degreasing and sandblasting roughening. The degreasing process involves ultrasonic cleaning in an acetone solution for 10 to 30 minutes. The sandblasting roughening process involves spraying white corundum abrasive onto the inner surface of the cookware at a pressure of 0.2 MPa to 0.6 MPa, with a spraying distance of 100 mm to 200 mm and a spraying angle of 60° to 90°. The resulting surface roughness Ra is 2.5 μm to 6.5 μm.
9. The method for preparing a durable non-stick coating for cookware based on an amorphous alloy according to claim 1, characterized in that, After the supersonic flame spraying method deposits the composite coating and before the pulsed electron beam irradiation treatment, the composite coating is further subjected to a pre-polishing treatment. The pre-polishing treatment uses diamond polishing paste with a particle size of 0.5μm~2μm for mechanical polishing for 5min~20min. After polishing, the surface roughness Ra of the composite coating is reduced to 0.8μm~2.0μm.
10. The method for preparing a durable non-stick coating for cookware based on an amorphous alloy according to claim 1, characterized in that, After the pulsed electron beam irradiation treatment is completed and cooled to room temperature, the surface coating is further subjected to fluorination treatment. The fluorination treatment is as follows: the cookware is placed in a vacuum heating furnace, and an F2 / N2 mixed gas with a flow rate of 50 mL / min to 200 mL / min is introduced, wherein the volume fraction of F2 is 5% to 20%, and heated to 150℃ to 350℃ and held for 30 min to 120 min, thereby forming a metal fluoride surface layer with a thickness of 2 nm to 20 nm on the surface coating.